The impact of utilizing waste tires and plastic on concrete pavement performance and environmental benefits - Ahmad M. Abu Abdo; S. J. Jung; Hany El Naggar (Journal of Asian Architecture and Building Engineering)
This study focuses on the integration of sustainable practices in construction projects by utilizing waste materials like waste plastic and rubber tires, specifically in Portland Cement Concrete (PCC) mixes. While adding plastic waste fibers (PF) has shown to enhance the performance of rigid pavements, the environmental and cost benefits are limited. On the other hand, using tire-derived aggregates (TDA) compromises the mechanical properties of PCC but offers significant environmental advantages and cost reductions. This study explores the outcomes of combining PF and TDA in PCC mixtures, assessing their impact on pavement performance through KENPAVE software, which evaluates deflections and cracking indices. Additionally, the environmental and cost effects of this combination are analyzed using the PaLATE 2.0 software, aiming to develop sustainable and economically viable rigid pavements.